THE RELATIONSHIP BETWEEN HOME ENVIRONMENTAL CONDITIONS AND THE INCIDENCE OF ISPA IN CHILDREN UNDER FIVE IN THE WORKING AREA OF THE PULAU BANYAK HEALTH CENTER, ACEH SINGKIL REGENCY - Anjasmara, Rizki; Hamisah, Irma; Mawardi, Mawardi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Acute Respiratory Infection (ISPA) is one of the main causes of death, killing ± 4 million children under five every year. Banyak Island showed an increase in ISPA cases from 8.5% in 2017, increasing to 10.4% in 2018, and in 2019 it increased to 16.4% of toddlers experiencing ISPA. The research aims to determine the relationship between home environmental conditions and the incidence of acute respiratory infections in children under five in the Pulau Banyak Health Center Working Area, Aceh Singkil Regency. Method: This research is descriptive analytical with a case-control design. Data collection was carried out by interviews using questionnaires. The population in this study was 60 toddlers and the sample was determined using a total sampling technique, namely 60 toddlers. This research was conducted on 02 -16 November 2020. The statistical test used was the Chi Square Test (α=95%). Results: The results of univariate research showed that toddlers who experienced Acute Respiratory Infection (ISPA) (50%), ventilation did not meet the requirements (81.5%), overcrowding (82.1%), and smoking habits (80.8%). The results of bivariate statistical tests obtained ventilation (p value=0.001, OR=13.7), occupant density (p value=0.002, OR=16.4), and smoking habits (p value=0.001, OR=11.7) with the incidence of Acute Respiratory Infection in toddlers in the Pulau Banyak Health Center Working Area, Aceh Singkil Regency. The results of this research show a relationship between ventilation, occupant density, and smoking habits with the incidence of Acute Respiratory Infection in toddlers in the Pulau Banyak Health Center Working Area, Aceh Singkil Regency. Recommendation: It is recommended that the Pulau Banyak Community Health Center can improve the early alert system for ISPA incidents by increasing mothers' knowledge, attitudes, and behavior regarding the importance of healthy physical sanitation at home.